Wonder cat Kyuu-chan. 3 - Nitori, Sasami (Seven Seas Entertainment, 2021)
Presents the graphic novel adventures of Kyuu-chan the wonder cat and its owner, Hinata. Here Kyuu-chan learns how to make popcorn and do laundry, while Hinata comes to enjoy exercise. Also features the return of Ghost-kun.